Theoretical aspects of reengineering the business processes of construction enterprises - Zaiets А. (Ways to Improve Construction Efficiency, 2019)
This article offers the theoretical aspects of reengineering the business processes of construction enterprises. There are determined the essence, role and necessity of reengineering the business processes. There was revealed the stages of reengineering, the observance of which is a necessary condition of efficiency of realization of reengineering the business processes for a construction enterprise.